2019
DOI: 10.1093/isp/ekz014
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Using Role-Play Simulations with Chinese Students in China

Abstract: A significant body of literature testifies to the effectiveness of role-play gaming and simulations as pedagogical methods in political science. Many of these studies involve students with a Western background. In contrast, little research exists on the teaching of political science in China and none on the effectiveness of simulations for teaching Chinese students. This study seeks to investigate the efficacy of role-play simulations as a method for teaching comparative politics to Chinese students. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies indicate that simulations do contribute to retention in general (Baranowski, 2006;Parmentier, 2013;Leib and Ruppel, 2020). Specifically, studies indicate that role-playing simulations contribute to both short-term retention (Cruz-Martinez, Soto and Belén Benito, 2022) and long-term retention (Smith and Boyer, 1996;Toomey, Zhou and Yan, 2020). Ultimately, Youde (2008, 348) reports that ''students retain more information, gain a deeper understanding of an issue (though this may come at the expense of breadth), examine issues from a wider range of perspectives, and generally report having more fun in class'' Simulations provide benefits but create unique challenges in their implementation.…”
Section: Using Simulationsmentioning
confidence: 99%
“…Studies indicate that simulations do contribute to retention in general (Baranowski, 2006;Parmentier, 2013;Leib and Ruppel, 2020). Specifically, studies indicate that role-playing simulations contribute to both short-term retention (Cruz-Martinez, Soto and Belén Benito, 2022) and long-term retention (Smith and Boyer, 1996;Toomey, Zhou and Yan, 2020). Ultimately, Youde (2008, 348) reports that ''students retain more information, gain a deeper understanding of an issue (though this may come at the expense of breadth), examine issues from a wider range of perspectives, and generally report having more fun in class'' Simulations provide benefits but create unique challenges in their implementation.…”
Section: Using Simulationsmentioning
confidence: 99%
“…It is worth noticing how the literature on the use of simulations tends to be focused on Western classrooms. Some recent exceptions are Meschoulam et al (2019) and Toomey et al (2019).…”
Section: The Model United Nations As a Role-playing Simulationmentioning
confidence: 99%
“…Simulations are especially beneficial to law enforcement officers as they prepare them for emergency preparedness training (Miller et al, 2014); police crisis management (Uddin et al, 2020); handling of traffic accidents (Nepelski & Struniawski, 2019); and in developing improved police communications services (Greasley & Smith, 2017). Additionally, simulations also appear in different formats from the physical (Byrne, 2018), to gaming activities (Bonde et al, 2014); and role-playing scenarios (Toomey et al, 2020;Ahmadov, 2011). Furthermore, researchers observed that performance on midterm and final test scores improved after the introduction of an active learning method in the Criminal Justice field (Lysne & Miller, (2017).…”
Section: Introductionmentioning
confidence: 99%